Limit Behaviour of Solutions to a Class of Equivalued Surface Boundary Value Problems for Parabolic Equations (Journal of Partial Differential Equations, 2000)
In this paper, we discuss the limit behaviour of solutions for a class of equivalued surface boundary value problems for parabolic equations. When the equivalued surface boundary \overline{Γ}^ε_1 shrinks to a fixed point on boundary Γ_1, only homogeneous Neumann boundary conditions or Neumann boundary conditions with Dirac function appear on Γ_1.
Keywords: Parabolic equations; equivalued surface; limit behaviour; Dirac function